Optimizing Job Placement and Training Programswith Pega Decisioning Solutions - Sai Kiran Nandipati (North American Journal of Engineering Research, 2021)
Unemployment poses significant socio-economic challenges globally, prompting governments to seek innovative solutions to improve job placement and training programs. This paper explores how Pega decisioning solutions can enhance the efficiency and effectiveness of these programs. Leveraging advanced technologies such as predictive analytics, adaptive analytics, personalized recommendations, and automated workflows, Pega solutions offer a promising approach to optimizing jobplacement and training outcomes. Through a mixed-methods approach, combining quantitative data analysis with qualitative case studies, this study examines the impact of Pega decisioning solutions on program performance. The findings demonstrate significant improvements in job placement rates, program efficiency, and user satisfaction. Additionally, the study identifies challenges in implementation and provides strategies to address them. The implications of these findings suggest that similar technological solutions can be applied across various public services to improve efficiency and effectiveness. This research contributes valuable insights for policymakers, practitioners, and researchers interested in leveraging technology to address unemployment and enhance workforce development.